RELATIONSHIP BETWEEN ACADEMIC PROCRASTINATION AND CAREER ASPIRATION AMONG UNDERGRADUATE STUDENTS: A STUDY - Dr.Vidhu Shekhar Pandey, Dr. Swangi (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2023)
The present study is an attempt to study the relationship between Academic Procrastination and Career Aspiration among undergraduate students. Sample for the study consisted of 200 undergraduate students from CMP PG College and RBS Degree college, Prayagraj, U.P. Academic Procrastination Scale (2018) developed by S. Gupta and L. Bashir and self-constructed Career Aspiration Scale were used as tools for the study. Product moment coefficient of correlation have been computed for the analysis of the data. The findings of the present study revealed that Academic Procrastination is negatively related to Career Aspiration among undergraduate students; Academic Procrastination is negatively related to Career Aspiration among male and female undergraduate students; Academic Procrastination is negatively related to Career Aspiration among urban and rural undergraduate students; and Academic Procrastination is negatively related to Career Aspiration among Arts, Science and Commerce undergraduate students.